Performance Measurement Using Balanced Scorecard (BSC) (Study at Hospitals in Pasuruan) - Taufik, Abd Rahman; Djamhuri, Ali; Saraswati, Erwin (Journal of Accounting and Business Education, 2018)
Balanced scorecard (BSC) is a performance measurement method which is applied to private organizations to balance between financial and nonfinancial aspects. However, in this case, the financial measure of BSC application to non-profit public sector organizations is very different from private organizations. This study aims at measuring the performance of hospitals in Pasuruan based on four BSC perspectives (financial perspective, customer perspective, internal business process perspective,and learning and growth perspective). This study was conducted at the hospital using secondary data in the form of financial reports and non-financial reports. The object of this research was the hospitals in Pasuruan. The results showed that the performance of the three hospitals in Pasuruan in using BCS gauge is good. This reflects that the three hospitals in Pasuruan always strive to realize the achievement of vision, mission, and goals as one of the optimal public health services in Pasuruan and surrounding areas.